Tumor sólido pseudopapilar de páncreas - Walter Salinas; Marcos Marani; Santiago Reimondez; Alvaro Alcaraz; Franco Signorini; Martin Maraschio; Enzo A. Giordano; Lucio R. Obeide (Permanyer, 2021)
Solid pseudopapillary tumor of the pancreas is a rare entity, more frequent in women between the 2nd and 4th decades. The diagnosis is usually incidental and it can be reached by computed tomography or magnetic resonance imaging. Subsequent pathological confirmation is necessary for an adequate treatment. A retrospective study of six cases was carried out. All the patients were female, between 14 and 56 years of age, in which 50% the tumor were an incidental finding. We had three cases located in the head and three in the body of the pancreas. We performed three pancreaticoduodenectomies and three distal pancreatectomies with splenic preservation, without disease recurrence